Stability control of humanoid biped robot using PID controllers - Lam, Zhi Kien; Sheikh Muhammad Hafiz Fahami, Zaina (Penerbit UMP, 2023)
As technology has advanced, the usage of robots has become a major worldwide issue, especially for robots that interact with people. Humanoid biped robots have the potential to function as people's helpers, capable of assisting society and replacing humans in various or dangerous tasks. However, despite advances in robotic stability control, robust control for a broad variety of applications remains a difficulty. The purpose of this research is to look at optimum control techniques for stability control in humanoid biped robots in order to obtain superior stability. To regulate the robot's stability, several control techniques such as Proportional-Integral-Derivative control, Proportional-Integral control, Proportional-Derivative control, and Linear Quadratic Regulator (LQR) are utilised. Before implementing these control techniques, the humanoid biped robot's open loop system is evaluated to determine its stability response. To investigate the system response of robot stability control, the MATLAB programme is used.